Study of the Motion Performance of Marine Current Power Plant Turbine Floaters Due To Ocean Current Forces under Moored Conditions - Kasharjanto, Afian; Erwandi, Erwandi; Marta, Eko; irawanto, Zulis; Rahuna, Daif; SJM, Cahyadi (Department of Naval Architecture - Diponegoro University, 2023)
Indonesia targets carbon emissions to reach 0% in 2060 and is replaced by optimizing the use of renewable energy sources. Indonesia as an archipelago country, with the potential of thousands of straits can be utilized as a source of ocean currents as a source of electrical energy. The electricity generated is obtained from a turbine rotor that rotates due to the force of the ocean current flow. To support the turbine rotor to move in the sea, a floating support structure is needed. In this study, a trimaran tipe support structure is used where on the left and right sides are installed 2 (pieces) turbine rotors @ 50 kW each, so that the total has a capability of 200 kW (@4 x 50 kW). The novelty of this study is the utilization of Trimaran technology in marine current power generation turbines, which has good stability, low resistance, and a wider deck area rather than monohull structures. A numerical study using Computational Fluid Dynamics (CFD) is used to calculate the program. The results showed that the floater only moves backward and then is pulled forward with a small amplitude of movement in the X-direction, while those on the Y and Z axes are insignificant. The turbine floater can be immediately stabilized and the turbine rotor will rotate due to the force of the ocean current received. Therefore, in this study, the marine current turbine using trimaran type is showing good ability to survive in Indonesian waters even in high current areas.